The Effect Of The Group Investigation (GI) Learning Model On Students' Critical Thinking Ability In Geography Subjects - Andrinata (Pesantren Reviews, 2023)
This study focuses on experiments to find out the relationship of the Group Investigation (GI) learning model to students' critical thinking skills in Geography Subject at MA Al-Khoiriyah, Bojonegoro Regency. This research seeks to overcome the lack of students' critical thinking skills through appropriate cooperative learning models so that they can hone the critical thinking skills of MA Al-Khoiriyah students, Bojonegoro Regency. The GI learning model emphasizes students to be more active than teachers in line with the curriculum policy currently implemented in schools, namely student-centered learning (student center). The 2013 curriculum uses a scientific approach which consists of observing, asking questions, exploring information, associating, and communicating. This is very consistent with the steps implemented in the GI learning model. The steps contained in the GI learning model require students to carry out joint investigations with their groups. The results of the group investigation were then presented in front of the class and then as the final step an evaluation was carried out together with the teacher. The teacher's role in this learning model only acts as a companion. The results of using the Group Investigation (GI) learning model affect the critical thinking skills of class XI IIS students at Ma Al-khoiriyah Bojonegoro in Geography subject. This is shown by the test results in the experimental class having a higher average value than the control class.